2013
DOI: 10.1080/10408398.2011.596292
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability and Potential Uses of Vegetarian Sources of Omega-3 Fatty Acids: A Review of the Literature

Abstract: Presently alpha-linolenic acid (ALA) is the most widely used vegetarian LC3PUFA, but only marginal amounts are converted into eicosapentaenoic (EPA) and docosahexaenoic acid (DHA); both of which are strongly related to human health. Currently, fish oils represent the most prominent dietary sources of EPA and DHA; however, these are unsuitable for vegetarians. Alternative sources include flaxseed, echium, walnut, and algal oil but their conversion to EPA and DHA must be considered. The present systematic review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(68 citation statements)
references
References 38 publications
0
59
0
5
Order By: Relevance
“…Although part of α-linolenic acid is theoretically converted to EPA and DHA, recent research has shown that conversion is often low and this is in particular true for DHA. 9 Bioavailability of FAs can vary significantly depending on their various chemical forms, for example, natural triglycerides, re-esterified triglycerides or ethyl esters. 18 Not only the type of chemical bonds but also the concomitant intake of food affect the uptake of LC n-3 PUFAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although part of α-linolenic acid is theoretically converted to EPA and DHA, recent research has shown that conversion is often low and this is in particular true for DHA. 9 Bioavailability of FAs can vary significantly depending on their various chemical forms, for example, natural triglycerides, re-esterified triglycerides or ethyl esters. 18 Not only the type of chemical bonds but also the concomitant intake of food affect the uptake of LC n-3 PUFAs.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] It should be mentioned here that α-linolenic acid frequently found in seeds and plant oils is another potential source of EPA and DHA; however, the conversion rate (especially to DHA) is considered to be very low. 9 Considering the low consumption of seafood products in large parts of the population, attempts have been made to fortify food accordingly or to produce dietary supplements with LC n-3 PUFAs from marine sources. It has been shown that enriched foods with LC n-3 PUFAs increase plasma phospholipid DHA and EPA.…”
Section: Introductionmentioning
confidence: 99%
“…Fortified snack bars also delivered equivalent amounts of DHA on a DHA dose basis (Arterburn et al 2007). A systematic review of plant omega-3 fatty sources by Lane et al (2014) concluded that further research on algal sources was warranted based on promising preliminary work.…”
Section: Lipidsmentioning
confidence: 99%
“…Among bioactive ingredients, n-6 and n-3 PUFA serve as the primary components of biologi-cal structures in the cell membranes of higher mammals (Hulbert et al, 2005) and are also well recognized as essential elements in the human diet (Vella et al, 2013;Ganesanet al, 2014). Among these n-3 PUFA, eicosapentaenoic acid (EPA), docohexaenoic acid (DHA), and α-linolenic acid (ALA) are the most important (Lane et al, 2014). Eicosapentaenoic acid and DHA are mainly found in marine sources such as fish, fish oils, and algae (El Abed et al, 2008;Iafelice et al, 2008;Bermúdez-Aguirre and Barbosa-Cánovas, 2011), whereas ALA is commonly found in vegetable sources such as flaxseed, walnut, and echium seed oils (DeFilippis and Sperling, 2006;Iafelice et al, 2008;Bermùdez-Aguirre and Barbosa-Cánovas, 2012).…”
Section: Introductionmentioning
confidence: 99%